The Implementation of Akhlakul Karimah Values in Islamic Religious Education Learning - Hanafie Das, St.Wardah; Wisriani, Wisriani; Ruslan, Ruslan (Universitas Muhammadiyah Enrekang, 2025)
Akhlakul karimah refers to noble character that reflects faith in Allah SWT and positive interactions with fellow human beings. The purpose of this paper is to explain the concept of akhlakul karimah, the methods of its implementation in Islamic Religious Education (PAI) learning, and the factors influencing the success of its implementation. The method used in writing this paper is a literature study, referring to books, journals, and relevant literature on Islamic character education. The discussion results indicate that the implementation of akhlakul karimah in PAI learning can be carried out through the habituation of positive behaviors, contextual learning, teachers’ role modeling, and the integration of moral values into daily activities. The success of implementing the values of akhlakul karimah is influenced by internal factors of students, the family environment, school culture, community support, as well as challenges posed by digital media. This paper is expected to serve as a reference for PAI teachers, schools, and parents in effectively instilling Islamic moral values in students.